Resolução do problema de mercado de energia elétrica brasileiro e análise de remuneração dos serviços ancilares de compensação síncrona e reserva operativa - Espindula, Carla Jacobsen (2021)
Society has evolved, and new technological and digital inventions have become extremely important in people's lives. As a result, the guarantee of a continuous supply of electricity, safely and reliably, has become an essential service for the consumer. Ancillary services, such as the control of frequency and voltage of the electrical system, for example, are necessary and, if not performed correctly, can lead to instability and even total system collapse. Given the importance of these controls and their peculiarities, the remuneration of ancillary services must be made separate from the operating costs. To minimize the transmission system operation costs and to create a fairer analysis of ancillary services remuneration, in this work, two mathematical models of the electric energy market optimization problem are presented. The operating costs to satisfy the demand of the loads and the active power losses of the electric power system are considered, together with the costs of operating power reserve and synchronous compensation ancillary services. The models developed in this work are based on the operating rules and procedures of the National Electric System Operator and the Chamber for the Commercialization of Electric Energy of Brazil. The difference between the models lies in the proposal for the second model, which stipulates a new form of remuneration for reactive power generation, in which remuneration schemes are more structured and attractive to the electricity market and recent changes in the electricity sector. To demonstrate the effectiveness of the proposed new scheme, the IEEE 30 test system is used for simulation and analysis in AMPL software, using the KNITRO optimization package, which applies a variant of the branch and bound method. Finally, it can be demonstrated that the electric system operator is better benefited by the market model proposed in the second model, due to the reduction of operating costs and the more attractive and transparent way of pricing the reactive power costs inserted in the system.